Cord blood CD34+ cells expanded on Wharton's jelly multipotent mesenchymal stromal cells improve the hematopoietic engraftment in NOD/SCID mice. (26th May 2014) - Milazzo, Luisa; Vulcano, Francesca; Barca, Alessandra; Macioce, Giampiero; Paldino, Emanuela; Rossi, Stefania; Ciccarelli, Carmela; Hassan, Hamisa J.; Giampaolo, Adele
Abstract Objective This study aims to investigate the capability of Wharton's jelly multipotent mesenchymal stromal cells (WJ‐MSC) to support the in vitro expansion of hematopoietic stem/progenitor cells (HSPC) derived from cord blood (CB) in the absence of exogenous cytokines, and the effect on engraftment of the expanded cells in a mouse model. Methods CB‐CD34+ cells were seeded on WJ‐MSC layer and cultured in HP01 serum‐free medium. Day‐7 and day‐13 expanded cells were transplanted in NOD/SCID mice. After 8 wk, engraftment was evaluated in mouse bone marrow as percentage of human CD45+ cells. Results CD34+ population was expanded without increasing the differentiation rate. Co‐culture increased the expansion of the CD34+ cells by 2.0 and 7.3 times after 7 and 13 d, respectively, and maintained the CD34+ cells up to day 20. In particular, earlier CD34+/CD90+ and CD34+/CD33− subtypes were increased. An advantage of the day‐7 co‐cultured HSPC in respect of HSPC at day 0 in the engraftment of NOD/SCID mice was obtained both as percentage of mice engrafted (100% vs. 75%) and as percentage of chimerism. Conclusions Although the increase in hematopoietic progenitors is not dramatic as in the presence of added cytokines, this study demonstrates the effectiveness of the WJ‐MSC not only to preserve the CD34+ population but also to improve the repopulating efficacy of the amplified HSPC, also in the absence of added cytokines and growth factors.